Exploring Entrepreneurial Intention among Business Students at Yarmouk University in Jordan - Melhem, Yahya; Al Shaikh, Fuad (Jordan Journal of Business Administration, 2016)
The purpose of this paper is to investigate entrepreneurship intention of Yarmouk University business students in order to identify their readiness for future entrepreneurship challenges. A questionnaire was distributed to collect primary data from respondents who were selected randomly. A total of 400 questionnaires were distributed. Two hundred seventy-nine questionnaires were returned with a response rate of 69.7%. The results showed that the level of entrepreneurship intention among business students is 4.80 on a 7-point scale. They also revealed that the age of respondent is not significant in relation to entrepreneurship intention, while gender has a significant impact on entrepreneurship readiness, with higher intention among male respondents. Finally, the results also demonstrated that taking one course in entrepreneurship is not sufficient to have a significant impact on entrepreneurship intention among business students in Jordan. The study concluded with significant implications for staff and students to foster entrepreneurial intention among business students before employment.